PEMBELAJARAN MUSIK DAERAH SETEMPAT DI SMP NEGERI 6 KOTA PADANG - Winda Febrianti Sari; Ardipal Ardipal; Syahrel Syahrel (FBS Universitas Negeri Padang, 2012)
The purposeof this research is to describethe strategy, planning, implementation, and evaluationof music learning daerah setempat atJunior High School 6 in Padang city.This research isa qualitativeresearch by applying a methodof descriptive analysis. The object of the research is the Music strategiesLearning at the daerah setempat. The datawere collectedby observation, interview, library study,anddocumentation. This research was interactively analyzed,such as collecting the data, clarifying the data,organizingthe findings, and drawing a conclusion. The result of research is that cultural-art teacher of junior high school 6 Padang who specially teach at the class of VII-2 have the strategy in the process of learning at the class. The applied strategy is full class learning. Kata kunci: pembelajaran, musik daerah setempat